Crinum asiaticum (BOTANI, PEMANFAATAN DAN BIOAKTIVITAS) - Silalahi, Marina (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
Crinum asiaticum is a type of Amarallydaceae has been long used as a traditional medicine. The purpose of this article is to explain the relationship between the use of C. asiaticum as a traditional medicine and its bioactivity. The method used in writing the article is a literature review on some research published online using the keyword C. asiaticum, uses of C. asiaticum and bioactivities of C. asiaticum. The results obtained were then synthesized to explain the utilization and bioactivity of C. asiaticum. The traditional medicine of C. asiaticum is used to treat fever, treat fractures, sprains, inflammation and treat back pain. C. asiaticum has bioactivity as an antioxidant, antidiabetic mellitus, antimicrobial, anti-cancer, anti-inflammatory, analgesic and anti-urolytic. Licorin, crinamin and 6-hydroxycrinamine are compounds that are responsible for anti-cancer, so it is potential to be developed as an alternative anti-cancer because they are easily found in the environment.